2015
DOI: 10.1007/s10802-015-9985-y
|View full text |Cite
|
Sign up to set email alerts
|

Negative Trauma Appraisals and PTSD Symptoms in Sri Lankan Adolescents

Abstract: The cognitive model posits that negative appraisals play an important role in posttraumatic stress disorder, in children as well as in adults. This study examined correlates of negative appraisals in relation to trauma exposure and their relationship to posttraumatic stress symptoms (PTSS) in 414 Sri Lankan adolescents, aged 12 to 16, living in areas impacted in varying degrees by the 2004 tsunami. In 2008, participants completed measures of negative appraisals, lifetime traumatic events, posttraumatic stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
(65 reference statements)
1
21
0
Order By: Relevance
“…A large body of literature documents that children exposed to disasters are at risk for developing mental health symptoms (Dogan, 2011; Lai, Alisic, Lewis, & Ronan, 2016; Lai, La Greca, & Llabre, 2014). Posttraumatic stress symptoms (PTSS) are the primary presenting mental health problem among children after disasters (Dyregrov & Yule, 2006; Furr, Comer, Edmunds, & Kendall, 2010; Lai, Kelley, Harrison, Thompson, & Self-Brown, 2015b; Ponnamperuma & Nicolson, 2016). More research is needed that addresses how to mitigate the mental health consequences of disasters for children.…”
mentioning
confidence: 99%
“…A large body of literature documents that children exposed to disasters are at risk for developing mental health symptoms (Dogan, 2011; Lai, Alisic, Lewis, & Ronan, 2016; Lai, La Greca, & Llabre, 2014). Posttraumatic stress symptoms (PTSS) are the primary presenting mental health problem among children after disasters (Dyregrov & Yule, 2006; Furr, Comer, Edmunds, & Kendall, 2010; Lai, Kelley, Harrison, Thompson, & Self-Brown, 2015b; Ponnamperuma & Nicolson, 2016). More research is needed that addresses how to mitigate the mental health consequences of disasters for children.…”
mentioning
confidence: 99%
“…Similarly, information processing models of anxiety and traumatic stress apply this appraisal process to the development of PTSS, such that threatening appraisals of the traumatic event (in this case, injury) can lead to behavioral strategies (e.g., avoidance) that directly contribute to PTSS and/or prevent the development of longer-term realistic and adaptive appraisals (Ehlers & Clark, 2000; Meiser-Stedman, 2002). These models have been expanded from adults to children, with consideration of possible developmental changes in how children encode and resolve trauma memories (Dalgleish, Meiser-Stedman, & Smith, 2005; Meiser-Stedman 2002; Ponnamperuma and Nicolson, 2015; Salmon & Bryant 2002). For example, one investigation found global negative appraisals (i.e., how they experienced their worst events in the past month) to be the best predictor of PTSS in adolescents who experienced multiple traumas resulting from a tsunami, explaining 22% of the variance in concurrent PTSS (Ponnamperuma & Nicolson, 2015).…”
mentioning
confidence: 99%
“…These models have been expanded from adults to children, with consideration of possible developmental changes in how children encode and resolve trauma memories (Dalgleish, Meiser-Stedman, & Smith, 2005; Meiser-Stedman 2002; Ponnamperuma and Nicolson, 2015; Salmon & Bryant 2002). For example, one investigation found global negative appraisals (i.e., how they experienced their worst events in the past month) to be the best predictor of PTSS in adolescents who experienced multiple traumas resulting from a tsunami, explaining 22% of the variance in concurrent PTSS (Ponnamperuma & Nicolson, 2015). Hitchcock and colleagues (2015) also identified a strong role for appraisals (i.e., disturbing and permanent change/ feelings of fragility/believing the world to be scary post-trauma exposure) of a single incident trauma and its consequences in predicting PTSS in youth: Appraisals mediated the relationship between social support and PTSS.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that post-traumatic cognitions are predictive of the severity and chronicity of PTSD symptoms (Hitchcock, 2015;Liu & Chen, 2015;Ma et al, 2011;Palosaari et al, 2013;Ponnamperuma & Nicolson, 2016), and may play an influential role in the maintenance of PTSD. In a longitudinal study with war-exposed Palestinian children aged 10-12 years, Palosaari et al (2013) found that high levels of post-traumatic cognitions at 3 months post exposure to trauma significantly predicted a worsening of PTSD symptoms 5 and 11 months post-trauma.…”
Section: Distorted Cognitions About the Trauma And Negative Beliefs/ementioning
confidence: 99%